Diagnosing economic security of an industrial enterprise - Kasyanova, N.V.; Kasyanov, A.V. (Економіка промисловості, 2014)
In the article it is shown, that the basic methodological approaches to the analysis of the probability of bankruptcy industry, have different imperfections. The necessity of appraisal of the crisis on the basis of weak signals and early prediction of potential crisis, leaded to the creation of the model diagnosis of the industrial enterprises' crisis, which is based on an analysis of all components of economic security, and allows us to estimate the depth of the crisis the company. Assessment of the level of economic security is done from the perspective of the several components that characterize the presence of the crisis at the enterprise and the use of certain elements of the economic potential of the enterprise. To estimate the signal intensity of the loss of economic security, it is proposed to use the theory of fuzzy sets. The mechanism of calculating the integral indicator of the economic security level, which reflects the efficiency of the economic potential of the company was given. Also, it should be noted, that the method of analysis of economic security may be subject to adjustment in the context of the analyzed enterprise specifics and characteristics of the industry. The paper addresses important scientific and practical tasks for the formation of the methodological approach for the level of economic security diagnosing. The main practical recommendations for the use of given research is to use the algorithm of choice strategy of crisis management now, depending on the depth of the crisis and identifying elements of economic security for its respective recess.